UMP researchers shines at PECIPTA 2015 - UMP, PNC (Penerbit UMP, 2015)
Universiti Malaysia Pahang (UMP) won big at the International Invention Conference and Exhibition 2015 (PECIPTA 2015) which positioned the university among the best universities with its scores of five gold medals, three silver medals and three bronze medals. PECIPTA 2015 was held in Kuala Lumpur Convention Centre (KLCC) on December 4-6, 2015.